Compliance Analysis of Health Protocol Compliance with Covid-19 Vaccination Review from Knowledge and Family Health Maintenance Functions in Mulyorejo Village Balen Bojonegoro - Ahmad Zainal Abidin; Yusuf Efendi (East Asian Journal of Multidisciplinary Research, 2022)
Coronavirus Disease of 2019 which is still a world health threat because it has a huge impact on all aspects of human life, this must be controlled with comprehensive handling including vaccination efforts and also compliance in implementing the Covid-19 health protocol. In carrying out this research with quantitative methods, with the data collection process using a questionnaire. The study analyzed adherence to the post-covid-19 health protocol in terms of knowledge and family health maintenance functions. The result of this study is that compliance in carrying out the post-covid-19 health protocol is more related to knowledge than the function of maintaining family health. So it is very important for each individual to maintain the quality of his knowledge supported by the function of maintaining family health in the face of the COVID-19 pandemic.